Large-scale inhomogeneities in modified Chaplygin gas cosmologies - Chimento, Luis Pascual (2005)
We extend the homogeneous modified Chaplygin cosmologies to large-scale perturbations by formulating a Zeldovich-like approximation. We show that the model interpolates between an epoch with a soft equation of state and a de Sitter phase, and that in the intermediate regime its matter content is simply the sum of dust and a cosmological constant. We then study how the large-scale inhomogeneities evolve and compare the results with cold dark matter (CDM), ΛCDM and generalized Chaplygin scenarios. We find that unlike that like the latter, our models resemble ΛCDM.